2016
DOI: 10.1177/1557988315579096
|View full text |Cite
|
Sign up to set email alerts
|

Boy Crisis? Sex Differences in Self-Injurious Behaviors and the Effects of Gender Role Conflicts Among College Students in China

Abstract: In Western research, self-injurious behaviors are commonly viewed as "feminine" behavior. In this present study, using the data from a survey administered to 960 first-and second-year students in Xi'an Jiaotong University in China, the self-injurious behaviors among college students are analyzed by sex. The results reported that the average prevalence of self-injurious behaviors among male students is 35.2%, higher than the 20.4% observed among female students (p < .1), and the average frequency of severe self… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
12
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 35 publications
3
12
1
2
Order By: Relevance
“…There are no clear and consistent gender differences in NSSI behaviors among Chinese middle-school students, and only two studies have explored this aspect ( Chao, Yang, & Luo, 2016 ; Yang & Feldman, 2017 ). First, a survey was conducted among undergraduate students in a university of northwest China in 2013, which showed that the prevalence of these behaviors among male students (25.2%) was significantly higher than among female students (20.4%).…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…There are no clear and consistent gender differences in NSSI behaviors among Chinese middle-school students, and only two studies have explored this aspect ( Chao, Yang, & Luo, 2016 ; Yang & Feldman, 2017 ). First, a survey was conducted among undergraduate students in a university of northwest China in 2013, which showed that the prevalence of these behaviors among male students (25.2%) was significantly higher than among female students (20.4%).…”
mentioning
confidence: 99%
“…First, a survey was conducted among undergraduate students in a university of northwest China in 2013, which showed that the prevalence of these behaviors among male students (25.2%) was significantly higher than among female students (20.4%). This suggested a crisis among males in the prevalence of NSSI behaviors among adolescents in China ( Chao, Yang, & Luo, 2016 ). Second, a literature review was conducted on NSSI behaviors in Chinese people from Chinese and English literature databases, and a meta-analysis was carried out on gender differences in the prevalence of these behaviors.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…While the former tended to be domestically located, the latter is increasingly located within education. For example, social research Chao et al, 2015) has particularly focused on education, highlighting the wider societyÕs anxiety that Ôboys are becoming more girlyÕ. Recent spectacular media accounts of Ôfeminised boysÕ are resonant of a projected US/UK/Australian concern about the war on boys (Sommers, 2000;Haywood et al, 2015).…”
Section: Introductionmentioning
confidence: 99%